2007
DOI: 10.1002/chin.200732207
|View full text |Cite
|
Sign up to set email alerts
|

5‐Alkynyl‐2′‐deoxyuridines: Chromatography‐Free Synthesis and Cytotoxicity Evaluation Against Human Breast Cancer Cells.

Abstract: Nucleic acids U 0700 5-Alkynyl-2'-deoxyuridines: Chromatography-Free Synthesis and Cytotoxicity Evaluation Against Human Breast Cancer Cells. -(MENENI, S.; OTT, I.; SERGEANT, C. D.; SNIADY, A.; GUST, R.; DEMBINSKI*, R.; Bioorg. Med. Chem. 15 (2007) 8, 3082-3088; Dep. Chem., Oakland Univ., Rochester, MI 48309, USA; Eng.) -Bartels 32-207

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…For this technique, two critical steps are identified: (1) ethynyl deoxyuridine toxicity for some cell lines is higher in comparison to BrdU and (2) the kinetic conditions for alkyneazide cycloaddition are important. EdU has been reported to have antiviral activities, but also affects cell proliferation by inhibition of thymidilate synthetase and deoxynucleoside kinase activity (Cristofoli et al, 2007;Meneni et al, 2007). EdU concentrations used for this assay ideally should be assessed for each cellular model.…”
Section: Critical Parameters and Troubleshootingmentioning
confidence: 99%
“…For this technique, two critical steps are identified: (1) ethynyl deoxyuridine toxicity for some cell lines is higher in comparison to BrdU and (2) the kinetic conditions for alkyneazide cycloaddition are important. EdU has been reported to have antiviral activities, but also affects cell proliferation by inhibition of thymidilate synthetase and deoxynucleoside kinase activity (Cristofoli et al, 2007;Meneni et al, 2007). EdU concentrations used for this assay ideally should be assessed for each cellular model.…”
Section: Critical Parameters and Troubleshootingmentioning
confidence: 99%
“…On the other hand, the use of EdU and EdC is complicated by their cytotoxicity [16][17][18][19][20][21][22]. Although it was shown that the EdC toxicity is lower than that of EdU [5], the reason was not known.…”
Section: Introductionmentioning
confidence: 99%